2021
DOI: 10.33140/coa.06.01.04
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Spot Urinary Chloride Concentration Measurements in Patients with Acute Heart Failure: Investigation on the Basis of the ‘TubuloGlomerular Feedback’ Mechanism

Abstract: Urinary chloride (Cl) is the key electrolyte for regulating renin secretion at the macula densa under the ‘tubulo-glomerular feedback’. Whether or not Cl filtrated into the urinary tubules actually associates with plasma renin activity (PRA) in clinical heart failure (HF) remains unclear. Data from 29 patients with acute worsening HF (48% men; 80.3±12 years) were analyzed. Blood and urine samples were immediately obtained before decongestive therapy after the patients rested in a supine position for 20-min. Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…While uNa + has received substantial attention as an indicator of resistance to diuretic treatment and worsening HF symptoms leading to increased mortality 28 30 , uCl − has been overlooked as a valuable biomarker, despite its significant role in HF pathophysiology 31 . Most previous studies regarding Cl − have primarily focused on serum concentration 7 , and to the best of our knowledge, our study is among the few to explore the relationship between uCl − and patient outcomes 32 , 33 . Our analysis of urine biomarkers reveals a positive correlation between all analyzed electrolytes, consistent with trends observed in serum levels.…”
Section: Discussionmentioning
confidence: 99%
“…While uNa + has received substantial attention as an indicator of resistance to diuretic treatment and worsening HF symptoms leading to increased mortality 28 30 , uCl − has been overlooked as a valuable biomarker, despite its significant role in HF pathophysiology 31 . Most previous studies regarding Cl − have primarily focused on serum concentration 7 , and to the best of our knowledge, our study is among the few to explore the relationship between uCl − and patient outcomes 32 , 33 . Our analysis of urine biomarkers reveals a positive correlation between all analyzed electrolytes, consistent with trends observed in serum levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, hypochloremia in turn induces renin secretion, increases the expression and activity of sodium-potassium-chloride cotransporters as well as sodium-chloride cotransporters, and promotes electrolytes reabsorption leading to diuretic resistance ( 25 ). Several studies have demonstrated that low serum chloride is apparently associated with neurohormonal activation and diuretic resistance, leading to impaired decongestive diuretic efficacy in patients with heart failure, which in turn increases the risk of death and readmission ( 26 , 27 ). This may be a common consequence of hypochloremia.…”
Section: Discussionmentioning
confidence: 99%